Properties of matter and energy (McGraw-Hill School Division, 2000)
Discover what matter is, and is not. Learn about and the difference between a mixture and a solution. Chocked full with hands on activities to understand the various physical and chemical changes to matter. Our resource provides ready-to-use information and activities for remedial students using simplified language and vocabulary. Written to grade these science concepts are presented in a way that makes them more accessible to students and easier to understand. Our resource is jam-packed with experiments, reading passages, and activities all for students in grades 5 to 8. Overhead transparencies and answer key included and can be used effectively for your whole-class.